The Effect of Banking Financial Ratios on Firm Value (An Empirical Study on Conventional Banking Companies Listed on The Indonesia Stock Exchange for The 2018-2022 Period) - Jonardy, Medika Julia; Avionita, Venni (Badan Penerbit Fakultas Ekonomi dan Bisnis Universitas Singaperbangsa Karawang, 2024)
The study population comprises conventional banking companies listed on the IDX durung the 2018-2022 period, with samples selected using purposive sampling techniques. This research employs non-participant observation techniques for data collection, utilizin secondary data form the annual reports of each company published on their official websites. The data analysis techniques used in this study are descriptive and verificaive statistics, including multiple regression analysis and hypothesis testing with partial and simultaneous statistical tests. The results of this study show that; 1) Partially, Return On Equity (ROE) has a positive and significant effect on Firm Value. 2) Partially, Capital Adequacy Ratio (CAR) has a positive and significant effect on Firm Value. 3) Partially, Loan to Deposit Ratio (LDR) has a negative and significant effect on Firm Value. 4) Simultaneously, ROE, CAR, and LDR have a significant effect on Firm Value.